Predictors of non-response to successive waves of surveys in the Japan Environment and Children’s Study during the 3-year postpartum period: a longitudinal cohort study - Mika Kigawa; Akiko Tsuchida; Tomomi Tanaka; Kei Hamazaki; Yuichi Adachi; Hidekuni Inadera; Kenta Matsumura; Haruka Kasamatsu (BMJ Open)
Objectives We examined changes in factors related to non-response to successive waves of the nationwide birth cohort study, the Japan Environment and Children’s Study (JECS), during the first 3 years after childbirth.Design Longitudinal cohort study.Setting As the baseline survey, mothers completed self-administered questionnaires distributed by hand during pregnancy or 1 month after delivery. The self-administered questionnaires that we used in this study were then distributed by mail every 6 months until the children were 3 years old, for a total of six times.Participants Of 103 060 mothers who consented to participate in the JECS during pregnancy, 88 489 mothers were included in the study after excluding those with multiple births, miscarriages or stillbirths and those who withdrew from the study within 3 years after providing informed consent.Primary and secondary outcome measures Data were collected at the baseline survey on participants’ socioeconomic status, medical history, health status, health-related behaviours and their children’s health conditions and living situations. The strength of the impact of related factors and the prediction of response status were examined and compared using binominal logistic regression analysis.Results For all six follow-up questionnaire surveys, higher maternal age was strongly associated with providing a response. Factors that were strongly associated with mothers not providing a response were smoking after childbirth and having more children. The concordance rate of response status based on the presented model was about 70%, suggesting that the response status for the first 3 years after birth can be predicted from the information collected in the baseline survey.Conclusion By identifying predictors of non-response from information obtained in baseline surveys, researchers may be able to reduce non-response to successive survey waves by issuing reminders, reviewing data collection methods and providing appropriate financial and/or non-financial incentives.